The Issue of Security in the Balkans in the Context of the Soviet-French Negotiations on the Eastern Pact (1933–1935) - Alexandrovich Vershinin, Alexander (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
The author argues that the Balkans, although not a direct participant in the negotiations on the Eastern Pact between the USSR and France in 1933–1935, played an important role in its final realization. Paris considered the Balkans the cornerstone of a complex system of collective security, ensuring the interconnection of its Mediterranean and Eastern European zones. Moscow saw the Balkan region as a potential door for anti-Soviet intervention and was interested in strengthening its positions there by penetrating the French system. At the same time, the normalization of relations between the USSR and the Balkan countries enabled the Soviet leadership to exert diplomatic pressure on France. By the end of 1933, both sides found a mutually acceptable scenario of diplomatic rapprochement, which made it possible to plan the long-term stabilization of relations in Eastern and South-eastern Europe in 1934. However, the murder of J. L. Barthou in October 1934, as well as the new course of his successor, prevented the successful completion of the process, although it enabled the USSR to gain diplomatic recognition from a number of Balkan states.
Keywords: Eastern Pact; 1935 Franco-Soviet Treaty of Mutual Assistance; Little Entente; Balkan Pact; M. M. Litvinov; J. L. Barthou; collective security